1994
DOI: 10.1128/jvi.68.2.704-712.1994
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of the Vif protein of human immunodeficiency virus type 1

Abstract: Biochemical characteristics of the association of Vif with cellular membranes and its membrane topology were also examined. These studies also investigate the roles of the N and C termini and highly conserved regions of Vif in membrane targeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 48 publications
6
78
0
Order By: Relevance
“…Formation of the viral particles is therefore probably normal, allowing the analysis of the role of vif during the late steps of virus replication. The fact that the Vif protein has been localized to the cytoplasmic side of the cellular membranes (12) supports the results presented in the present study: vif acts at the level of particle formation. This observation raises some additional questions; for example, on which modification and on which viral or cellular target protein does Vif act?…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Formation of the viral particles is therefore probably normal, allowing the analysis of the role of vif during the late steps of virus replication. The fact that the Vif protein has been localized to the cytoplasmic side of the cellular membranes (12) supports the results presented in the present study: vif acts at the level of particle formation. This observation raises some additional questions; for example, on which modification and on which viral or cellular target protein does Vif act?…”
Section: Discussionsupporting
confidence: 92%
“…It encodes a 23-kDa protein which is absent from virions but present in infected cells (17). Recent observations have indicated that HIV-1 Vif is located in the cytoplasm both in a cytosolic form and associated with the cytoplasmic side of cellular membranes (12). This protein is encoded by all lentivirus genomes except that of equine infectious anemia virus (19) and is antigenic, since antibodies against Vif are detected in the sera of infected individuals (1,17).…”
mentioning
confidence: 99%
“…A cocultivation method was used to produce large quantities of wild-type and vif mutant virus in a nonpermissive CEM cell line (11,14). Infection of CEM cells was initiated by cocultivation with COS cells transfected with 5 g of wild-type or vif mutant HXB2 DNA by the DEAE-dextran method (14,18) from 36 to 72 h after transfection. Infection of SupT1 cells was initiated by DEAE-dextran transfection with 10 g of viral DNA (14).…”
Section: Methodsmentioning
confidence: 99%
“…HAtagged hA3G was probed with a mouse anti-HA (Sigma) monoclonal antibody at a dilution of 1:5000. For HIV-1 Vif detection, a rabbit anti-Vif polyclonal antibody (Goncalves et al, 1994) was used at a 1:2000 dilution. The secondary antibody was a sheep anti-mouse or donkey anti-rabbit horseradish peroxidase-(HRP) conjugated antibody (Invitrogen), both at 1:5000 dilutions.…”
Section: Western Immunoblotmentioning
confidence: 99%